The Flexible Organizational Structure and Its Role in Developing Administrative Skills from the Perspective of Administrators of Several Sports Clubs in Erbil Governorate (Journal of the College of Basic Education, 2025)
The research aimed to identify the role of a flexible organizational structure in developing the administrative skills of a number of sports clubs in Erbil Governorate. The descriptive approach, using a survey method and correlational relationships, was used due to its suitability to the nature of the current research. The research community included (150) administrative cadres representing a number of sports club administrators in Erbil Governorate. The researcher used (10) administrators to conduct the exploratory experiment, while (10) questionnaires were neglected due to the lack of scientific requirements. To achieve the research objectives, a questionnaire was constructed with two axes: the first, the flexible organizational structure, and the second, the development of administrative skills, in accordance with scientific procedures. The data were processed statistically using the SPSS system, which included the arithmetic mean, standard deviation, percentage, Pearson's correlation coefficient, and Cronbach's alpha. The researcher reached several conclusions, the most important of which is that most of the paragraphs of the dimensions of the first axis (decentralization, low formality, simplification) obtained (high) percentages, and most of the paragraphs of the dimensions of the second axis of the questionnaire (technical skills, intellectual skills, human skills, communication, decision-making, evaluation) obtained (good) percentages, confirming the importance of administrative skills in achieving the flexible organizational structure's goals.